Java 17 for absolute beginners : learn the fundamentals of Java programming - Cosmina, Iuliana (Apress, 2022)
Write your first code in Java 17 using simple, step-by-step examples that model real-word objects and events, making learning easy. With Java 17 for Absolute Beginners you'll be able to pick up the concepts without fuss. It teaches Java development in language anyone can understand, giving you the best possible start. You'll see clear code descriptions and layout so that you can get your code running as soon as possible. Author Iuliana Cosmina focuses on practical knowledge and getting you up to speed quickly-all the bits and pieces a novice needs to get started programming in Java. First, you'll discover what type of language Java is, what it is good for, and how it is executed. With the theory out of the way, you'll install Java, choose an editor such as IntelliJ IDEA, and write your first simple Java program. Along the way you'll compile and execute this program so it can run on any platform that supports Java. As part of this tutorial you'll see how to write high-quality code by following conventions and respecting well-known programming principles, making your projects more professional and efficient. Java 17 for Absolute Beginners gives you all you need to start your Java programming journey. No experience necessary. After reading this book, you'll come away with the basics to get started writing programs in Java. What You Will Learn Get started with Java 17 from scratch Use data types, operators, and the stream API Install and use the IntelliJ IDEA and the Gradle build tool Exchange data using the new JSON APIs Play with images using multi-resolution APIs Implement the publish-subscribe architecture Who This Book Is For Those who are new to programming and who want to start with Java.